Clean Up of Fluoride Rich Effluents by the China Clay - Lonare, Rekha; Inam, Farhin; Deo, S. (Asian Journal of Chemistry, 2010)
Fluoride concentration in water has significant importance. Fluoride is beneficial when present in concentration of 0.5-0.8 ppm. But fluoride has been associated with mottled enamel of the teeth in concentrations in excess of 1.5 mg/L. The adsorption of fluoride on China clay was investigated in the present study. The parameters studied include the contact time, setting time, pH, dose of absorbent, rate of stirring and initial adsorbate concentration of fluoride removal efficiency. The optimized sorbent dose was found to be 1.5 g/100 mL equilibrium was achieved in 2 h and maximum adsorption was obtained at pH 3. Freundlich adsorption isotherms were plotted and kinetic constants were determined.